2020 IEEE 28th Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM) 2020
DOI: 10.1109/fccm48280.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Systolic-CNN: An OpenCL-defined Scalable Run-time-flexible FPGA Accelerator Architecture for Accelerating Convolutional Neural Network Inference in Cloud/Edge Computing

Abstract: This paper presents Systolic-CNN, an OpenCL-defined scalable, runtime-flexible FPGA accelerator architecture, optimized for accelerating the inference of various convolutional neural networks (CNNs) in multi-tenancy cloud/edge computing. The existing OpenCLdefined FPGA accelerators for CNN inference are insufficient due to limited flexibility for supporting multiple CNN models at run time and poor scalability resulting in underutilized FPGA resources and limited computational parallelism. Systolic-CNN adopts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Related work is shown by (Han et al, 2016), which results into reduced power consumption by reducing number of weights. More higher level of optimization is proposed by (Dua et al, 2020), which uses the OpenGL compiler for DNNs, such as VGG and AlexNet. Hah et al (2019) suggested framework for automatic conversion of deep neural network models into intermediate format (HLS) and then subsequent FPGA implementation.…”
Section: Related Workmentioning
confidence: 99%
“…Related work is shown by (Han et al, 2016), which results into reduced power consumption by reducing number of weights. More higher level of optimization is proposed by (Dua et al, 2020), which uses the OpenGL compiler for DNNs, such as VGG and AlexNet. Hah et al (2019) suggested framework for automatic conversion of deep neural network models into intermediate format (HLS) and then subsequent FPGA implementation.…”
Section: Related Workmentioning
confidence: 99%